Effects of Temperature and Salinity on the LMS (Lysosomal Membrane Stability) Biomarker in Clams Donax trunculus and Chamelea gallina - Paula Soms-Molina; Concepción Martínez-Gómez; Esther Zuñiga; Miguel Rodilla; Silvia Falco (Applied Sciences, 2024)
Population of clams Donax trunculus and Chamelea gallina have been declining significantly in recent decades, and environmental pollution and accelerated global warming have been proposed as contributing factors to this decline, in addition to overfishing. Lysosomal membrane stability (LMS) is a sensitive indicator of health status of the organisms. In this study, we investigate the LMS in these species after exposure for 21 days to nine combined conditions of water temperature (12, 20, and 27.5 °C) and salinity ranges (27–28, 32–33, and 37–38). LMS was assessed in living hemocytes by using the neutral red retention assay. Mortality and the condition index of the organisms were evaluated as supporting parameters. The results indicated interspecies differences in the LMS under similar environmental conditions. Overall, LMS was found to be more sensitive to temperature than to salinity changes. Although both species can tolerate changes in either salinity or temperature seawater conditions, the tolerance range is narrower for D. trunculus, showing a significant cytotoxicity (NRRT < 50 min) at temperatures above 27.5 °C and salinities above 32, and 100% mortality at 27.5 °C and a low salinity range (27–28). This study is the first to assess the combined effect of temperature and salinity on the LMS in C. gallina and D. trunculus, and provide necessary information before using LMS as contaminant-related biomarker in field studies with these species.